Mitigating the Impact of Flood Disaster Risk in Wonoasri Village, Tempurejo District, Jember Regency - Setiawan, Rendy; Krisnamurti; Luh Putu Indah Budyawati; Anik Suwandari; Galih Wicaksono; Haris Cahyono; Syafira Lailatul Ulfa Marfuah (Faculty of Mathematics and Natural Sciences, University of Jember. Jl. Kalimantan No.37, Krajan Timur, Jemberlor, Kec. Sumbersari, Jember Regency, East Java 68121, 2024)
Flooding is a natural disaster that often occurs in several village areas in Tempurejo Sub-district, Jember Regency, one of which is in Wonoasri Village. Residents of Wonoasri Village have carried out regular prevention activities every rainy season, one of which is the construction of river bunds and dredging mud. However, if not seriously anticipated, the flood disaster will paralyse access to the village. The purpose of this service is to inform insights and preventive mitigation actions related to flood disasters to the village community and especially to the Wonoasri Disaster Response Village (Destana) team. This activity is composed of several activities including the provision of equipment grants, training and socialisation, and evaluation of activities. The results of this activity are the provision of insights and handling actions by the Destana Wonoasri team related to flood management and the operation of equipment grants. Participants were very interested in this activity organised by the community service team, so it is hoped that this event in the future can be a positive thing for the village community and the Destana Wonoasri team to deal with natural disasters, especially floods.